(untitled) (International Conference on Computers in Education, 2022)
Learning by teaching someone else has proven to be beneficial in both human-human and human-agent interaction. Instructing someone else, that is, taking the role as a tutor, has a series of positive effects on students’ learning and performance. For example, the fact that someone else is in need of help seems to affect students to put more effort into the task at hand, trying harder, being more thorough and persisting longer. This has inspired researchers to design educational software that uses teachable agents (TAs). The use of such software has shown to improve students’ – not the least lower-achieving students’ – learning. Designing teachable agents is, however, a delicate matter since the personality and capability of the agent may affect students’ behaviors and performance. This study, which includes data from 156 6th grade students who used an educational game in history during three lessons, contributes to research on how students’ perceptions of a neutral TA (without any specific personality and behavior) may influence their performance. The focus is on whether and how students’ learning gains are influenced by the extent to which students perceive their TA as someone who does need their help. In addition, we explored whether such potential effects would differ between lower- and higher-achieving students. Results were that students’ perceptions about the TA’s need for help was a significant predictor of high performance (based on in-game performance and post-test scores) – independent of their general achievement level (grounded in the students’ reading proficiency). In other words, all students, whether lower- or higher-achieving, benefitted from being convinced of the agent’s need for help. This finding is somewhat different from previous studies, where TAs mainly have been found to be beneficial for lower-achieving students. In relation to this, the present study adds a novel piece of information by suggesting that for TAs to be beneficial in educational software, their need for help should be clearly communicated and emphasized. This, on the other hand, may make them useful for all students, independently of how well they usually perform in school.